Effect of water exchange rate on the growth performance and survival of kerai lampam, Hypsibarbus wetmorei x Barbonymus gonionotus - Roslan, Muhammad Faiz Syahmi (2013)
The effect of water exchange rate on the growth performance and survival of kerai lampam, Hypsibarbus wetmorei x Barbonymous gonionotus was studied. Effect of water exchange on water quality parameters was also investigated. The experiment was conducted for two months at the Aquaculture Research Station, Department of Aquaculture, Faculty of Agriculture, Universiti Putra Malaysia, Serdang, Selangor. The experiment involved four treatments. The treatments were zero water exchange (Treatment 1), daily water exchange (Treatment 2), weekly water exchange (Treatment 3) and once in two weeks water exchange (Treatment 4). Each treatment had four replicates. Each aquarium was filled with 60L of water. During water exchange, 30% of the aquarium water was replaced with dechlorinated tap water. Kerai lampam fingerlings were stocked at a density of 20 pieces/aquarium (333 fingerlings/m³). Artificial pellets with 42% protein were given at 5% of body weight. Kerai lampam fingerlings cultured in once in two weeks water exchange showed higher total weight gain (TWG) (1.29±0.15g), daily weight gain (DWG) (0.03±0.00g) and specific growth rate (SGR) (2.55±0.28g) compared to other treatments. However, in term of survival, no water exchange and daily water exchange showed the highest percentage of survival with 93.75%. DO was maintained above 4 mg/L, with temperature ranged between 25 to 27˚C and pH reading between 6.1 to 8.2. The TAN concentration throughout the experiment ranged between 0 to 2.63mg/L. No noticeable stress symptoms were observed on the fingerlings throughout the experimental period. Turbidity increased as the experiment progressed and ranged from 1.29 to 90.65NTU. Overall, it is recommended that under the studied stocking density and conditions, water exchange is not necessary to nurse kerai lampam fingerlings with acceptable growth for a period of 6 weeks.